Bidirectional relationship between mental health and sport injuries: a review of reviews - Gil-Caselles, L.; Ruiz Barquín, R.; Giménez Egido, J. M.; Olmedilla-Zafra, A. (Apunts Sports Medicine, 2024)
Mental health disorders are one of the most relevant problems in athletes and, as in the rest of the population, they seem to have increased since the COVID-19 pandemic. Sports injuries seem to be a relevant risk factor for mental health. The purpose of this review is to answer the relationship between sports injuries and mental health not only because of mental disorders, but also as generators of mental health deficits. A systematic review of the scientific literature was carried out following the PRISMA guidelines, the PICO strategy and interobserver concordance for quality control of the registry. Six databases were consulted, PubMed, Scielo, WebScience, Teseo, Dialnet and Scopus, selecting 12 review articles and 13 empirical articles. The results indicate that there is a significant relationship between mental health and sports injuries and that the symptomatology of mental health indicators in the athlete affects the injury or precedes it for a slower recovery. In conclusion, by checking the published scientific literature we can find a possible significant relationship between mental health and sports injuries that will help us to establish the current body of knowledge on this issue.